Relapsed Refractory Hodgkin Lymphoma and Brentuximab Vedotin-Bendamustine Combination Therapy as a Bridge to Transplantation: Real-World Evidence From a Middle-Income Setting and Literature Review - Radhakrishnan, Vivek S.; Bajaj, Rajat; Raina, Vasundhara; Kumar, Jeevan; Bhave, Saurabh J.; Sukumaran Nair, Reghu K.; Nag, Arijit; Arun, Indu; Zameer, Lateef; Dey, Debdeep; Arora, Neeraj; Parihar, Mayur; et al. (Frontiers in Oncology, 2022)
INTRODUCTION: Despite high cure rates with standard treatment, 30% patients with Hodgkin lymphoma develop relapsed or refractory (R/R) disease. Salvage therapy followed by autologous hematopoietic cell transplantation (HCT) is considered standard of care. Brentuximab Vedotin (Bv) in combination with Bendamustine (B) has been tested in the salvage setting with promising results. MATERIALS AND METHODOLOGY: We conducted a single centre retrospective chart review of patients who received BBv salvage therapy to determine its activity and safety in patients with R/R classical Hodgkin lymphoma (HL). Between May 2011- December 2019, 179 patients were diagnosed with R/R HL. RESULTS: Thirty patients received BBv [median age: 30 (15-59) years, females (n=15)]. Primary refractory disease in 19 patients (63%), and 26 patients (87%) had advanced stage at treatment. Most patients received BBv after 2 prior lines of therapy [n=16 (53%)]. The median number of cycles of BBv were 3 (1-6). The number of BBv cycles delivered as outpatient was 63%. The most common Grade III/IV hematological adverse event was neutropenia [n=21, (70%)], while grade III/IV non-hematological toxicities included infections in 4 (13%), neuropathy in 4(13%), skin rash in 2 (7%), GI toxicities in 3 (10%) and liver dysfunction in 2 (7%) patients. The ORR and CR rates were 79% and 62%, respectively. Seventeen patients (57%) underwent an autologous HCT and 8 (26%) underwent an Allogeneic HCT (all haploidentical). The median follow up time from BBv administration was 12 months. Six patients died: 2 = disease progression, and 4 = non-relapse causes (Infection and sepsis = 2, GVHD=2). In addition to this, one patient progressed soon after HCT and another patient relapsed 22 months post HCT. Three year Overall survival (OS) and Event free survival (EFS) probability post-BBv treatment was 75% and 58%, respectively. OS and EFS analysis based on response (viz., CMR) to BBv demonstrated that patients in CMR had better survival probability [93% (p=0.0022) 3yr-OS and 72% (p=0.038) 3yr-EFS probability]. CONCLUSIONS: BBv is an active and well-tolerated salvage treatment for patients with R/R HL, even in refractory and advanced settings. In middle-income settings, cost constraints and access determine patient uptake of this regimen.